Arabic language and globalization: duties to solutions; This article was published but is withdrawn on request of the author, therefore PDF has been removed. - Al-Omari, Husam Hassan Ahmad (Journal of Social Sciences (COES&RJ-JSS), 2021)
The research aims to identify the challenges facing the Arab countries in establishing their language in the information society and the era of globalization, and to show their impact on national unity, the duties of the Arab towards the language of his tongue and the language of his religion, and the future of the Arabic language in light of globalization in terms of the impact of globalization and its manifestations and the linguistic phenomena that it causes in the language, And some ways that would elevate the Arabic language locally and internationally, and some solutions and treatment methods to confront globalization, based on the descriptive and analytical approach. The research aims to identify the challenges that face the Arab countries in establishing their language in the information society and the era of globalization.